2015
DOI: 10.1111/tme.12221
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastography (TEG®) compared with total platelet count in thrombocytopenia haematological malignancy patients with bleeding: a pilot observational study

Abstract: Thrombocytopenic HM patients experiencing bleeding are hypocoaguable on TEG(®).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
3
14
1
Order By: Relevance
“…They found that both R‐time, alpha angle and MA were significantly different in patients with WHO bleeding events of grade ≥ 2 in the 24 h after the TEG analysis compared to non‐bleeding patients. They concluded that fibrinogen concentration may be an important component in relation to bleeding risk . As alpha angle is influenced by fibrinogen, this may be in line with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…They found that both R‐time, alpha angle and MA were significantly different in patients with WHO bleeding events of grade ≥ 2 in the 24 h after the TEG analysis compared to non‐bleeding patients. They concluded that fibrinogen concentration may be an important component in relation to bleeding risk . As alpha angle is influenced by fibrinogen, this may be in line with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Previous clinical studies have demonstrated hypocoagulable parameters (particularly reduced maximum amplitude) 15,24 in patients with severe thrombocytopenia despite no significant differences in PT and APTT, which is similar to our TEG ® experience. However, the data for thrombin generation are less clear with Álvarez-Román thrombomodulin.…”
Section: Discussionsupporting
confidence: 90%
“…Previous clinical studies have demonstrated hypocoagulable parameters (particularly reduced maximum amplitude) in patients with severe thrombocytopenia despite no significant differences in PT and APTT, which is similar to our TEG ® experience. However, the data for thrombin generation are less clear with Álvarez‐Román et al observing an elevated ETP (1696.4 vs 1223.8, P < 0.05) in 42 chronic ITP patients with platelet count <50 × 10 9 /L, in contrast to our ITP patients with marked thrombocytopenia.…”
Section: Discussionsupporting
confidence: 89%
“…The main difference between the studies is that this study includes pathogen‐reduced PCs, which reduce 1‐hour CCI without affecting ThromboLUX scores, but this does not explain the different findings because an analysis stratified for pathogen inactivation showed similar results. TEG measurements in hematooncologic patients correlate with bleeding tendency and show improved hemostatic functionality after transfusion, but our study showed no correlation between TEG measurements and 1‐hour CCIs. In line with literature, TEG measurements did not correlate with storage time, suggesting that this test is unable to monitor development of PSL and concomitant effects on 1‐hour CCIs.…”
Section: Discussioncontrasting
confidence: 78%